Performance Evaluation of MANET Routing Protocols AODV and DSDV Using NS2 Simulator - Amenah Mhmood; Ahmet Zengin (Sakarya University Journal of Computer and Information Sciences, 2021)
Mobile Ad hoc Network (MANET) is a collection of wireless mobile nodes that dynamically form a network temporarily without any support of central management. Moreover, every node in MANET moves arbitrarily making the multi-hop network topology to change randomly at uncertain times. There are several familiar routing protocols like AODV, DSR, and DSDV etc. which have been proposed for providing communication among all the nodes in the wireless network. This paper presents a performance comparison and study of reactive (AODV) and proactive (DSDV) protocols based on metrics such as throughput, packet delivery ratio, average end-to end delay, paket loss rate and consumed energy by using the NS-2 simulator. The simulation results showed that AODV performance is better than DSDV regarding packet delivery ratio and end to end delay, while DSDV performance is better than AODV regarding packet loss rate and consumed energy then the performance of AODV and DSDV protocls in throughput parameter is equal close. For small networks, DSDV works well and AODV is best suited for larger networks.